Synthesis and Characterization of [2+2] Cu(II) Macrocyclic Schiff Base Comp - Golbedaghi, Reza; Soudmand, Mehdi; Reza Keymanesh, Mahmoud; Veisi, Hojat; Azadbakht, Reza; Jaleh, Babak (Asian Journal of Chemistry, 2011)
[2+2]Cyclocondensation of L22py = N-(2-pyridylmethyl)-N-(2-aminoethyl)-1,2-diaminoethane, L23py = N-(2-pyridylmethyl)-N-(2-aminoethyl)-1,3-diaminopropane, L33py = N-(2-pyridylmethyl)- N-(3-aminopropyl)-1,3-diaminopropane} and 2,6-diformyl-4-methylphenol (dfp), in the presence of Cu(ClO4)2.4H2O in equimolar ratios gave three new binuclear Cu(II) macrocyclic complexes. Resulting compounds, [{Cu (H2L1) (H2O)}2](ClO4)4 (1), [{Cu (H2L2) (H2O)}2](ClO4)4 (2) and [{Cu (H2L3) (H2O)}2](ClO4)4 (3), were characterized by IR spectroscopy, elemental analysis and mass diffraction method. The Cu(II) ions in latter binuclear complex from penta-coordinated complexes.